A White Campion (Silene latifolia) floral expressed sequence tag (EST) library: annotation, EST-SSR characterization, transferability, and utility for comparative mapping - Marais Gabriel AB; Oger-Desfeux Christine; Moccia Maria; Widmer Alex (BMC Genomics, 2009)
Abstract Background Expressed sequence tag (EST) databases represent a valuable resource for the identification of genes in organisms with uncharacterized genomes and for development of molecular markers. One class of markers derived from EST sequences are simple sequence repeat (SSR) markers, also known as EST-SSRs. These are useful in plant genetic and evolutionary studies because they are located in transcribed genes and a putative function can often be inferred from homology searches. Another important feature of EST-SSR markers is their expected high level of transferability to related species that makes them very promising for comparative mapping. In the present study we constructed a normalized EST library from floral tissue of Silene latifolia with the aim to identify expressed genes and to develop polymorphic molecular markers. Results We obtained a total of 3662 high quality sequences from a normalized Silene cDNA library. These represent 3105 unigenes, with 73% of unigenes matching genes in other species. We found 255 sequences containing one or more SSR motifs. More than 60% of these SSRs were trinucleotides. A total of 30 microsatellite loci were identified from 106 ESTs having sufficient flanking sequences for primer design. The inheritance of these loci was tested via segregation analyses and their usefulness for linkage mapping was assessed in an interspecific cross. Tests for crossamplification of the EST-SSR loci in other Silene species established their applicability to related species. Conclusion The newly characterized genes and gene-derived markers from our Silene EST library represent a valuable genetic resource for future studies on Silene latifolia and related species. The polymorphism and transferability of EST-SSR markers facilitate comparative linkage mapping and analyses of genetic diversity in the genus Silene.